A methodology for the identification of significant factors for the improvement of pedestrian facilities in an urban area - V. Aromal; M. A. Naseer (Journal of Urban Management, 2022)
In many developing countries, comprehensive and structured planning strategies for pedestrians compared to users of other modes are grossly absent. This poses a challenge for planning agencies and local government authorities in the proper utilization of the fund. The purpose of this paper is to develop a comprehensive list of factors that would help in the decision-making process for the improvement of pedestrian facilities in urban areas. A preliminary list of 57 factors that influence the improvement of pedestrian facilities in the urban area was discovered through a literature survey and expert intervention. The compilation was done based on the frequency of citations in previous studies. The factors were then grouped into five major categories that characterize the pedestrian facilities such as (1) Infrastructure; (2) Location (3) Ambience/Liveability, (4) Safety and Security, and (5) Mobility. A Delphi survey was conducted among 24 selected experts. After 4 rounds of the survey, 33 factors were identified as significant for the improvement of pedestrian facilities in an urban area. The study also identified some significant factors that failed to get attention in the past. The consolidated list would serve as a guide for planners, authorities, and government officials to adopt significant factors according to their requirements, and can be used as a reference for other developing countries.
Keywords: 710; Delphi technique; Fund allocation; Indicator; Pedestrian; Ranking